Examining the Relationship between Actual Self and Ideal Self in Predicting the Tendency Toward Cosmetic Surgery in Young Women with Histrionic Personality Disorder - Asgharpour Miri, Maedeh; Moazami Goudarzi, Soheil (Psychology of Woman Journal, 2025)
Objective: This study aimed to investigate the relationship between actual self and ideal self in predicting the tendency toward cosmetic surgery among young women with histrionic personality disorder. Methods and Materials: This descriptive-correlational study was conducted on a sample of 100 young women aged 18 to 30 years residing in Babol, Iran, in 2024. Participants were selected using convenience sampling from those who had applied for or were on a waiting list for cosmetic surgery through public advertisements or psychological counseling centers. Data collection instruments included the Cosmetic Surgery Tendency Questionnaire (Soheili, 2017), the Ideal Self and Actual Self Assessment Questionnaire (Soodmand, 2004), and the MMPI for diagnosing histrionic personality disorder. Data were analyzed using SPSS-26 with Pearson correlation, multiple regression analysis, independent samples t-test, and structural equation modeling. Ethical standards such as informed consent, confidentiality, and voluntary participation were strictly observed. Findings: The results of Pearson correlation analysis indicated a moderate to strong positive relationship between the gap in actual and ideal self and the tendency toward cosmetic surgery (r = .55, p < .001), and a significant positive relationship between body image dissatisfaction and cosmetic surgery tendency (r = .48, p = .002). Multiple regression analysis showed that the gap between actual and ideal self (β = .55, p < .001), actual self (β = –.35, p = .01), and ideal self (β = .45, p = .001) significantly predicted the tendency toward cosmetic surgery. An independent t-test revealed that women with histrionic personality disorder had a significantly larger self-discrepancy (M = 2.75, SD = 0.60) than non-affected women (M = 1.50, SD = 0.45; p < .001). Conclusion: The findings suggest that self-discrepancy and body image dissatisfaction are significant psychological predictors of cosmetic surgery tendency among young women with histrionic personality disorder. These results highlight the need for targeted psychological interventions to enhance self-acceptance and reduce reliance on aesthetic modification as a means of emotional or social compensation.